THE FORMS OF FRESHMEN'S ADAPTATION DURING THE SESSION - Marina A. Krylova (Moscow Polytechnic University, 2016)
The empirical basis of this article are the materials of the research of freshmen's adaptation conducted within three years in several departments of Tver State University during the examination session. Research methods were participant observation, conversation, analysis of students' product activities. Identified variants (formulas) display two forms of students' adaptation - static and dynamic. Static forms of adaptation characterize orientation towards smoothing the inconsistencies between their own features and the conditions of life.Dynamic forms allow to convert the whole situation. The person using the dynamic variant ofadaptation becomes the subject of activity, because the conversion requires a high activity, personal attitude, ability to plan, monitor activity. There was offered a substantive interpretation of typical formulas of adaptation. Both forms of adaptation are considered as the indicators of successfulness of students' formation as subjects of education activity.